Influence of ensiled pineapple waste on microbial population and fermentation in the rumen of West African Dwarf rams (2015)
Pineapple waste (PW) is a by-product of pineapple processing industries. There has been the problem of disposal of the waste causing environmental pollution and health hazards. This study was conducted to harness PW into animal feed stuff to replace cassava peel in silages containing Panicum maximum and urea. A total of sixteen West African dwarf (WAD) rams weighing 11.50 ± 1.5kg were randomly allotted to four dietary treatments. The replacement rates were 90% PW, 60% PW, 30% PW and 0% PW respectively. Silages have very good physical characteristics of colour and texture with slightly acidic pH. Similarly, chemical analyses revealed increased dietary crude protein and crude fibre with PW replacement while dry matter was reversed. There were significant increase in the rumen pH which increased with PW inclusion. The same trend was obtained in rumen NH4-N (mg/dL) ranging from 3.69-7.18mg/dL and were significantly different across the treatments. The different volatile fatty acid (VFA) components had values that were statistically different and increased with the level of supplementation of PW. Lactic acid, butyric acid, propionic acid and acetic acid values ranged between 1.68-6.55, 0.74-4.46, 0.56-2.43, and 5.41-10.02 mg/dL, respectively. Fungi and bacteria population obtained for rams fed 4- hours post feeding showed that fungi population was highest at PW60 inclusion rate with an increase of 5.17cfu/ml amounting to 67.84%> and lowest at PWO which increased by 0.75cfu/ml amounting to 19.08%. Bacteria population increased as PW inclusion increased at 8.68, 4.73, 4.65, and 3.57cfu/ml, respectively. Therefore, PW could be ensiled and recycled for use in sheep diet thereby combating environmental pollution caused by the waste